Pelanggaran Asas Good Faith terhadap Perjanjian Nuclear Non-Proliferation Treaty (NPT) Oleh Korea Utara - Syarifatul Fadhilah; Amanda Fathona Fadhila; Universitas Bengkulu; Ema Septaria; M. Ilham Adepio (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines North Korea's violation of the principle of good faith under the Nuclear Non-Proliferation Treaty (NPT) and its legal consequences. The main issue addressed in this study is North Korea’s breach of the good faith principle within the framework of the NPT, which raises legal implications regarding its status and obligations as a party to the treaty. Although North Korea was formally bound by the NPT, it secretly developed a nuclear weapons program, demonstrating non-compliance with the fundamental principle of international treaty implementation. This issue was further exacerbated by its refusal to allow inspections by the International Atomic Energy Agency (IAEA) and its unilateral withdrawal from the NPT, which has sparked debate over the legitimacy and legality of such action.Using a normative juridical approach, this study analyzes North Korea’s clandestine development of nuclear weapons while still a member of the NPT, as well as the validity of its withdrawal from the treaty. The findings show that North Korea violated the principle of good faith through its secret nuclear program, refusal of IAEA inspections, and withdrawal that did not meet the requirements of Article X of the NPT. The withdrawal may be deemed invalid as it was conducted in bad faith and without fulfilling the treaty's formal provisions. The legal consequences include the continued applicability of obligations under the NPT and state responsibility for breaches of international law. Ideal forms of accountability include the cessation of the nuclear program, payment of reparations, guarantees of non-repetition, and renewed compliance with NPT provisions through verifiable denuclearization.